Improving the quality and efficiency of education and training in Costa Rica to better support growth and equity - Maravalle, Alessandro (OECD Publishing, 2023)
Education and training are a high priority for Costa Rica that devotes to them more than 6.5% of GDP, one of the highest spending shares among OECD countries. However, educational outcomes remain poor and firms struggle to fill their vacancies, particularly in technical and scientific positions, which may endanger Costa Rica's capacity to keep attracting foreign direct investment. Its complex fiscal situation requires Costa Rica to improve efficiency and quality of public spending in education to better support growth and equity. There is a fundamental need to improve the quality of early and general basic education to avoid that too many Costa Ricans leave education too early and without the skills needed to find a formal job. This requires a more targeted support to students with learning gaps, improving teachers' selection and training and expanding access to early education. Revisiting the university funding mechanism will improve its accountability and can help increase the number of graduates in scientific areas. Reforms in vocational education may increase the supply of high-quality technicians, which will reduce existing skills mismatches and help more Costa Ricans access better-paid formal jobs
Keywords: Economics; Costa Rica